Świadomość teoretycznoliteracka nauczycieli a efekty kierowania odbiorem dzieła literackiego = The Theoretical-Literary Consciousness of the Teacher and the Results in Supervising the Perception of a Literary Work - Marzec, Anna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
At issue is the influence of the theoretical-literary consciousness of the teacher on the results in supervising the perception of a literary work, going back to the tradition of twenty years between two world-wars, when a new attitude of mind arose in a climate of constant resistance, what can be shown by the example of LITERARY PARTITIONING IN SCHOOL by Mr. Kazimierz Wóycicki and by the biting polemics with his suggestions.
Keywords: dydaktyka literatury